2022
DOI: 10.1002/cnl2.28
|View full text |Cite
|
Sign up to set email alerts
|

Roles of interface engineering in performance optimization of skutterudite‐based thermoelectric materials

Abstract: Interface engineering has prevailed in the thermoelectric field for decades, and related performance has achieved great progress. Therefore, an in-depth understanding of the impacts of the interface effect on the thermoelectric transport parameters is of vital importance. In this paper, taking skutterudite-based thermoelectric materials as typical examples, the formation mechanism and preparation process of various interface types, including 1D dislocations, 2D grain refinement, 3D nanocomposites, and micro-na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…Liu et al developed a CoSb 3-x Te x structure by doping Te at the Sb site, which gave a high ZT value of 0.93 at 800 K due to an increased Fermi level and a large number of point defects produced in the solution. [33] When doping is done at the Co site by substituting Co with Ni, Pt, or Pd, some of the highest ZT values achieved are 0.6 for Co 3.8 Ni 0.2 Sb 12 at 800 K, 0.7 for Co 0.8 Ni 0.2 Sb 3 at 775 K, and 0.9 at 750 K for 5% Pd and 5% Pt-doped CoSb 3 , [34][35][36] and when doping is done at the Sb site with Te, Sn, Ge, and/or Se, the highest ZT values achieved are 0.98 at 820 K for CoSb 2.85 Te 0.15 and 1.1 for both CoSb 2.75 Ge 0.05 Te 0.2 and CoSb 2.75 Sn 0.05 Te 0.2 at 823 K and 820 K, respectively. [30,37,38] Some of the values are summarized in Table 1 below.…”
Section: Dopingmentioning
confidence: 99%
“…Liu et al developed a CoSb 3-x Te x structure by doping Te at the Sb site, which gave a high ZT value of 0.93 at 800 K due to an increased Fermi level and a large number of point defects produced in the solution. [33] When doping is done at the Co site by substituting Co with Ni, Pt, or Pd, some of the highest ZT values achieved are 0.6 for Co 3.8 Ni 0.2 Sb 12 at 800 K, 0.7 for Co 0.8 Ni 0.2 Sb 3 at 775 K, and 0.9 at 750 K for 5% Pd and 5% Pt-doped CoSb 3 , [34][35][36] and when doping is done at the Sb site with Te, Sn, Ge, and/or Se, the highest ZT values achieved are 0.98 at 820 K for CoSb 2.85 Te 0.15 and 1.1 for both CoSb 2.75 Ge 0.05 Te 0.2 and CoSb 2.75 Sn 0.05 Te 0.2 at 823 K and 820 K, respectively. [30,37,38] Some of the values are summarized in Table 1 below.…”
Section: Dopingmentioning
confidence: 99%
“…Among them, the CoSb 3 -based skutterudites exhibit favorable electrical transport properties due to their reasonable band gap. [13][14][15][16][17][18] However, the robust heat transmission capacity is closely related to their covalent framework, hindering the attainment of an ideal ZT value. Fortunately, filled-CoSb 3 addresses the optimal carrier concentration and suppresses lattice thermal conductivity (κ l ) simultaneously, thanks to its distinctive cage-like crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the thermoelectric properties of thin films, developing metal–semiconductor (M–Sc)-based composites offers a viable approach, extensively researched in the bulk forms of various thermoelectric materials. These composites effectively boost the electrical conduction through mechanisms such as carrier channeling, and carrier injection simultaneously suppresses phonon conduction by enhancing interfacial phonon scattering to achieve enhanced thermoelectric performance. ,, The influence of the metallic phase on σ is contingent upon the band structure of the matrix, the potential energy barrier at the interface between the two phases, and the electrical and thermal transport properties of the metallic phase. Also, the morphology, amount, and physical characteristics of the guest phase play a critical role in determining the resulting thermoelectric transport properties. , Previous studies had demonstrated the effect of metallic nanostructures in TE materials like (Bi,Sb) 2 (Te,Se) 3 , CoSb 3 , and MnSi 1.787 Al 0.0138 , where the selection of metallic inclusions with distinct work functions provides the perspective of a tunable barrier at the interface, promoting the electronic transport to tailor the TE properties. Consequently, the investigation of multiphase composite structures emerges as one of the most viable strategies to enhance the thermoelectric performance of existing materials.…”
Section: Introductionmentioning
confidence: 99%